La desprotección del estado a madres y padres de familia sin trabajo y que alimentan a infantes - Florencia Herrera, Jennit Elizabeth (2013)
This Thesis entitled "State DE protection of Mothers and Parents out of work and feed infants" prior to obtaining the title of Advocate of the Courts and Tribunals of the Republic of Ecuador was to carry out a proposed amendment to Article 17 of the Social Security Act. The analysis of problem areas, where it is shown how does the lack of a legal rule to include in this sector in preferential treatment program state, justified the conduct of this investigation. To this end, the objectives were drafted and hypothesis. In the theoretical framework developed scheme and updated relevant content according to their doctrinal context, case law and legislation, which hosted an analytical and description around the state social policy regarding the protection provided to vulnerable of society. The field research based on surveys and interviews, allowed to prove the hypothesis of the research, which was reached, demonstrate the need for reform of Article 17 of the Social Security Act in order to provide care for mothers and unemployed parents who are dedicated to caring for infants at home. The research findings showed that the work of this social sector should be considered as productive work, and as such, the center of attention by the state, allowing you to pay something face in their plight, not to, would maintain outdated policies of discrimination and social marginalization. Finally, the preamble and the legal basis provided the basis for the proposed amendment to Article 17 of the Social Security Act